SPECIATION OF FE(II) IN H2O-HCL-(CO2) FLUID AT 500-600°C AND A PRESSURE OF 2 KBAR - Tagirov B.R. (My University, 2001)
The solubility of the mineral associations hematite-magnetite (α-Fe2O3 + Fe3O4) and ferberitetungstite (FeWO4 + WO3) was studied in a system with hydrochloric acid activity controlled by the buffer Ag-AgCl-Fe2O3-Fe3O4 at 500-700°C, 2 kbar, and varying CO2 concentration (XCO2 = 0-0.3). The analysis of the solubility as a function of HCl concentration at 500°C and 2 kbar demonstrated the predominance of FeOHCl(aq)0 in pure water under such conditions (dlog m (Fe)d/log m (HCl) = 1). This species dominates at high water activity (high pressure and low carbon dioxide content). The species FeCl2(aq)0 is predominant in low-density fluids and at high CO2 contents. Iron-bearing mineral solubility in a mixed fluid at 600°C and 2 kbar was found to yield the values of the Born coefficient ω(FeCl2(aq)0) = (0.24±0.07)×105 and ω(FeOHCl(aq)0) = (0.86±0.20)×105 cal/mol. The logarithms of equilibrium constants were calculated for the following reactions: FeWO4 + HCl(aq)0 = FeOHCl(aq)0 + WO3 (500°C, 2 kbar), log K0 = -0.72±0.25; FeWO4 + 2HCl(aq)0 = FeCl2(aq)0 + WO3 + H2O (500°C, 2 kbar), log K0 = 0.58±0.35; Fe3O4 + HCl(aq)0 = FeOHCl(aq)0 + Fe2O3 (600°C, 2 kbar), log K0 = 0.43±0.20; and Fe3O4 + 2HCl(aq)0 = FeCl2(aq)2 + Fe2O3 (600°C, 2 kbar), log K0 = 1.61±0.25.